Design, synthesis, and biological evaluation of benzofuran- and 2, 3-dihydrobenzofuran-2-carboxylic acid N-(substituted)phenylamide derivatives as anticancer agents and inhibitors of NF-κB. Issue 12 (15th June 2015) - Choi, Minho; Jo, Hyeju; Park, Hyun-Jung; Sateesh Kumar, Arepalli; Lee, Joonkwang; Yun, Jieun; Kim, Youngsoo; Han, Sang-bae; Jung, Jae-Kyung; Cho, Jungsook; Lee, Kiho; Kwak, Jae-Hwan; et al.
Graphical abstract: Abstract: With the aim of developing novel scaffolds as anticancer agents and inhibitors of NF-κB activity, 60 novel benzofuran- and 2, 3-dihydrobenzofuran-2-carboxylic acid N- (substituted)phenylamide derivatives (1a –s, 2a –k, 3a –s, and4a –k ) were designed and synthesized from the reference lead compoundKL-1156, which is an inhibitor of NF-κB translocation to the nucleus in LPS-stimulated RAW 264.7 macrophage cells. The novel benzofuran- and 2, 3-dihydrobenzofuran-2-carboxamide derivatives exhibited potent cytotoxic activities (measured by the sulforhodamine B assay) at low micromolar concentrations against six human cancer cell lines: ACHN (renal), HCT15 (colon), MM231 (breast), NUGC-3 (gastric), NCI-H23 (lung), and PC-3 (prostate). In addition, these compounds also inhibited LPS-induced NF-κB transcriptional activity. The +M effect and hydrophobic groups on the N -phenyl ring potentiated the anticancer activity and NF-κB inhibitory activity, respectively. However, according to the results of structure–activity relationship studies, only benzofuran-2-carboxylic acid N -(4′-hydroxy)phenylamide (3m ) was the lead scaffold with both an outstanding anticancer activity and NF-κB inhibitory activity. This novel lead scaffold may be helpful for investigation of new anticancer agents that act through inactivation of NF-κB.